Comprensión lectora y rendimiento académico en comunicación de alumnos del segundo grado de una institución educativa de Ventanilla - Aliaga Jiménez, Lina Ysabel (2012)
This is a research aims to establish the relationship between reading comprehension and academic performance of the second grade students in a public school in Ventanilla. The sample consisted of 60 students from 7 and 8 years (28 males and 32 females). chosen intentionally. To evaluate the variable reading comprehension test 2 of Gloria Catalá. To measure the academic achievement in the area of comunication, we registered the final averages of the evaluation acts. We used the Spearman rank correlation coefficient. The investigation results show that there is a moderate positive relationship between both variables (r=0.662**) noting that students have good level of understanding literal and reorganized information; however they have a poor achievement in inferential and critical reading comprehension.